(untitled) (Contemporary Journal of Social Science Review, 2025)
The business life of Prophet Muhammad (SAW) and his companions (Sahaba) offers a profound model of ethical commerce rooted in integrity, trust, and social responsibility. This research paper explores the commercial practices of the Prophet (SAW) before and after prophethood, emphasizing his reputation as Al-Amin (the trustworthy) and how his principles transformed the moral landscape of trade in 7th-century Arabia. The study also delves into the business conduct of key companions, including Abu Bakr, Uthman ibn Affan, and Abdur-Rahman ibn Awf, who successfully balanced wealth accumulation with unwavering adherence to Islamic ethics. By analyzing authentic Hadith literature, historical accounts, and early Islamic sources, the paper highlights the core values that shaped the Islamic commercial ethos: honesty, fairness, fulfillment of contracts, prohibition of fraud, and emphasis on community welfare. It discusses how these principles were not merely theoretical but actively applied in marketplaces and trade networks, setting the foundation for Islamic economic thought. Additionally, the research investigates the socio-economic impact of the Prophet’s (SAW) guidance on trade, especially in promoting justice, discouraging monopolistic behavior, and encouraging charity through zakat and voluntary giving. The commercial lives of the Sahaba serve as case studies demonstrating the compatibility between spiritual devotion and economic success. The findings underscore the relevance of these early Islamic business practices in contemporary economic systems. They offer insights into creating ethical frameworks for modern businesses seeking to operate with integrity and social consciousness. Ultimately, this study aims to reintroduce the prophetic model of commerce as a viable and morally grounded alternative in today’s profit-driven markets.